Investigation of a green energy storage system based on liquid air energy storage (LAES) and high-temperature concentrated solar power (CSP): Energy, exergy, economic, and environmental (4E) assessments, along with a case study for San Diego, US. (December 2021) - Nabat, Mohammad Hossein; Soltani, M.; Razmi, Amir Reza; Nathwani, Jatin; Dusseault, M.B.
Highlights: A green hybrid system based on liquid air energy storage and concentrated solar power. A comprehensive and systematic evaluation of the proposed hybrid system. Achieving round trip energy and exergy efficiencies of 54.05% and 46.51%. Reaching a payback period of 2.06 years and total profit of 188.7 $M. Analyzing the system performance based on 8760 hourly real data in San Diego, the USA. Abstract: Liquid air energy storage, a recently introduced grid-scale energy storage technology, has attracted attention in recent years due to its unique characteristics: geographic location independence, high energy density, broad storage capacities, and fast response time. A green hybrid concept based on a combination of liquid air energy storage with concentrated solar power technology is evaluated through simulations to quantify the improvements in the environmental and operational performance of the system. In lieu of a conventional combustion chamber, a concentrated solar power combined with the heliostat field, cavity receiver, high-temperature molten salt, and thermal energy storage is used. During peak demand times, the system produces about 53.9 MW of power and 55 kg/s domestic hot water. The round-trip energy and exergy efficiencies of the system are 54.05% and 46.51%, respectively. Applying the proposed concept for the case of San Diego with the real hourly data, results in an annual green power generation of around 25 GWh, prevents the release of over 5100 tons of CO2, meaning an annual environmental cost reduction by over 122, 000 $. The economic analysis show that the payback period and overall profit of the proposed system in this city are 2.42 years and 137.4 $M, respectively.